Developing a model for measuring the spatial disability level of cities within the framework of barrier-free pedestrian accessibility: the case of Kırklareli City centre - Sinmaz, Serkan; Özkök, Mete Korhan (Budownictwo i Architektura / Civil and Architectural Engineering, 2024)
The problem of disability is directly related to the physical barriers encountered in urban spaces. Pedestrian accessibility performance is a notable urban quality indicator. Universal design principles and barrier-free design standards are important in making urban spaces usable for everyone. However, projects in this context generally cover specific areas of cities. Bringing an entire city into compliance with barrier-free design standards requires high cost and time. Therefore, determining the spatial disability level of the urban texture and planning project stages constitute a critical process for local governments. This study proposes a model to measure the pedestrian accessibility performance of medium-sized cities with relatively walkable distances within the framework of spatial barriers and to identify priority intervention points. In this context, Kırklareli city centre was selected as a case study area. According to the model developed with the support of GIS, the “ideal accessibility network” is determined for the citizens, and the performance level is calculated by identifying the spatial barriers on this network. The model was developed using components that can be applied to any city and tested in a sample urban environment. This conceptual model contributes to urban science and local government policy by providing a monitoring mechanism for spatial disability that can be constantly tracked by citizens, and by supplying an information base for projects to be developed by local governments. It is hoped that this study will popularise pedestrian-oriented spatial design and control in cities where walkability is postponed due to the focus on wheeled vehicle mobility and where spatial barriers are felt only by disabled individuals.